Health Care Spending and New Persistent Opioid Use After Surgery. Issue 1 (July 2020) - Lee, Jay S.; Vu, Joceline V.; Edelman, Anthony L.; Gunaseelan, Vidhya; Brummett, Chad M.; Englesbe, Michael J.; Waljee, Jennifer F.
Abstract : Objective: We sought to describe the differences in health care spending and utilization among patients who develop persistent postoperative opioid use. Summary of Background Data: Although persistent opioid use following surgery has garnered concern, its impact on health care costs and utilization remains unknown. Methods: We examined insurance claims among 133, 439 opioid-naive adults undergoing surgery. Outcomes included 6-month postoperative health care spending; proportion of spending attributable to admission, readmission, ambulatory or emergency care; monthly spending 6 months before and following surgery. We defined persistent opioid use as continued opioid fills beyond 3 months postoperatively. We used linear regression to estimate outcomes adjusting for clinical covariates. Results: In this cohort, 8103 patients developed persistent opioid use. For patients who underwent inpatient procedures, new persistent opioid use was associated with health care spending (+2700 per patient, P < 0.001) compared with patients who did not develop new persistent use. For patients who underwent outpatient procedures, new persistent opioid use was similarly correlated with higher health care spending (+1500 per patient, P < 0.001) compared with patients who did not develop new persistent use. Patients without persistent opioid use returned to baseline health care spending within 6 months, regardless of other complications. However, patients with persistent opioid use had sustained increases in spending by approximately 200 per month. Conclusion: Unlike other postoperative complications, persistent opioid use is associated with sustained increases in spending due to greater readmissions and ambulatory care visits. Early identification of patients vulnerable to persistent use may enhance the value of surgical care. Abstract : Supplemental Digital Content is available in the text